Destabilization of spin-Peierls phase via a charge-spin modulated Floquet state induced by intramolecular vibrational excitation - Daiki Sakai; Takashi Yamakawa; Hajime Ueda; Ryohei Ikeda; Tatsuya Miyamoto; Hiroshi Okamoto (Communications Physics, 2024)
Abstract The electronic state control using a periodic light field is one of the central subjects in photophysics. In molecular solids, intramolecular vibrations sometimes couple to intermolecular electron transfer, thus modulating electron and spin densities of each molecule. Here, we show that in a quasi-one-dimensional molecular solid K-tetracyanoquinodimethane (TCNQ) in which TCNQ molecules are dimerized by the spin-Peierls mechanism, an intramolecular vibrational excitation with a phase-locked mid-infrared pulse induces a charge-spin modulated Floquet state, which destabilizes the spin-Peierls phase. By detecting reflectivity changes of the intramolecular transition band along the mid-infrared electric field with 6.6-fs probe pulses, we detected high-frequency oscillations reflecting electron- and spin-density modulations synchronized with intramolecular vibrations. More significantly, we observed an oscillation of ~110 cm−1 due to a dimeric mode driven by a decrease in spin-Peierls dimerization. This dimerization reduction was confirmed by measuring transient reflectivity changes of the Mott-gap transition band. These results demonstrate the effectiveness of intramolecular vibrational excitation as a method for Floquet engineering in molecular solids.